2011
DOI: 10.1080/13548506.2011.580352
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for effectiveness of interventions to enhance coping among people living with HIV disease? A systematic review

Abstract: As new treatments enhance mortality, and infection rates continue to grow in many communities, the concept of "living well" with human immunodeficiency virus (HIV) infection is essential. The concept of coping has been well-articulated in the HIV literature and the public health argument for enhanced coping is crucial to reduce the burden of disease and health service use. This systematic review aimed to systematically identify and appraise the evidence for effectiveness in HIV coping interventions. A detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Adopting lifestyle modifications to maximize health (getting adequate nutrition and sleep, reducing substance use, adhering to medications, exercising, avoiding external stressors and ensuring financial security); establishing a sense of purpose in life; creating a daily structure or routine, and prioritizing tasks and planning for and anticipating the future, offer possible interventions clinicians may consider with their patients [15]. Specifically, cognitive-behavioral 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 and stress management interventions have been used to address anxiety and depression and enhance coping among people with HIV [56][57][58][62][63][64]. Overall findings highlight the importance for health providers and policy makers to consider the role of extrinsic and intrinsic contextual factors (programs, services and interventions) in addressing disability experienced by people living with HIV.…”
Section: Implications For Future Practice and Policymentioning
confidence: 99%
“…Adopting lifestyle modifications to maximize health (getting adequate nutrition and sleep, reducing substance use, adhering to medications, exercising, avoiding external stressors and ensuring financial security); establishing a sense of purpose in life; creating a daily structure or routine, and prioritizing tasks and planning for and anticipating the future, offer possible interventions clinicians may consider with their patients [15]. Specifically, cognitive-behavioral 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 and stress management interventions have been used to address anxiety and depression and enhance coping among people with HIV [56][57][58][62][63][64]. Overall findings highlight the importance for health providers and policy makers to consider the role of extrinsic and intrinsic contextual factors (programs, services and interventions) in addressing disability experienced by people living with HIV.…”
Section: Implications For Future Practice and Policymentioning
confidence: 99%
“…No study, however, has examined the frequency of their use as reported in a large number of empirical articles, although several studies have reviewed a small number of articles (e.g. Harding, Liu, Catalan, & Sherr, ). Several studies mention the frequency with which coping scales are used.…”
mentioning
confidence: 99%
“…While a concept of coping and its measures have been used in various contexts of coping, such as coping styles, strategies, and skills (Harding, Liu, Catalan, & Sherr, 2011), we use the term broadly to focus on positive aspects of dealing with HIV. In a review article, Ironson and Hayward (2008) examined evidence for the relationship between HIV disease progression and positive psychological constructs that included beliefs, positive affect, behaviors, personality dispositions, and social support.…”
mentioning
confidence: 99%